Juridical Review Of The Death Penalty In Indonesia In Islamic Law Perspective - Kurniawan Bagus Samudro (Law Development Journal, 2020)
This study aims to examine in depth the juridical review of capital punishment in Indonesia from the perspective of Islamic law. This research is expected to contribute ideas in the realm of literature in the field of Islamic law as well as input for observers and law enforcers to determine policies related to the death penalty law. To achieve the target, this research was conducted by observing events or facts that were considered relevant to the research, by collecting primary and secondary data through a juridical-normative approach with qualitative analysis methods. A study on this theme can be concluded that in the perspective of Islamic law, capital punishment (qisas) reflects justice and balance with the actions perpetrated by the perpetrator against the victim or the imposition of this punishment is in line with the principles of Islamic criminal law and the soul applies benefit to the level of social life. Public.Islamic law through Islamic criminal law (figh al-jinayat, at-tasri ul jinai) has guaranteed, protected and safeguarded the benefit of mankind by establishing a number of rules, either in the form of orders or prohibitions.Keywords: Death penalty; Islamic law; qisas; benefit.